The Managerial Competence Of The Madrasa Head In Improving Teacher Professionalism And Performance At Mi Al-Maarif Bojongsari, Cilacap District - Slamet Pamuji; Sun Limei (Yayasan Adra Karima Hubbi, 2023)
Background. Professional Madrasah Principals in the new paradigm of education management will have a positive impact and fundamental changes in the reform of the education system in Madrasas. Purpose. This quantitative study In addition to this, becoming a professional headmaster needs to start with a professional appointment as well. Method. This study uses a qualitative descriptive approach, namely research procedures that produce data descriptions in the form of words, spoken, or a person's behavior. Results. The result is that professionalism has good performance, so the competence of the principal here is very good in improving teacher performance and professionalism. a) Creating a program involving all school members is a form of leadership in human resources as human beings who need to be respected.. b) In achieving the school's vision and mission, the principal of the MI Al-Ma'arif Bojongsari school has delegated authority to teachers and administrative staff as a mirror of modified leadership. c) In improving the competence of pedagogic teachers, the principal of the MI Al-Ma'arif Bojongsari Conclusion. The efforts made by teachers in improving pedagogic competence are teachers have realized that the work of the teacher is a profession that needs to be improved. Efforts made by teachers in improving pedagogic competence, in addition to following the program that has been implemented by the school.